2022
DOI: 10.3390/biology11111580
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salinity Stress on Enzyme Activities, Histology, and Transcriptome of Silver Carp (Hypophthalmichthys molitrix)

Abstract: A 56-day study was performed to examine the effect of freshwater (FW) and brackish water (BW 6‰ salinity) on the antioxidant ability, Na+/K+-ATPase (NKA) activities, histology, and transcriptome of the gill and kidney tissue in juvenile silver carp (Hypophthalmichthys molitrix). The results show that when juvenile silver carp were exposed to 6‰ salinity, the activities of superoxide dismutase (SOD) and catalase (CAT) were shown to be substantially increased (p < 0.05), while glutathione peroxidase (GSH-PX) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…At the same time, there was no difference between GSH-Px levels in the high salinity group S3 and the GSH-Px levels of the freshwater group. These results are similar to those of studies on turbot (Scophthalmus maximus) [22], where CAT and GSH-Px work together to degrade hydrogen peroxide in high-salinity environments. In low-salinity environments where fish do not experience significant oxidative stress, GSH-PX does not rise to the same level as in freshwater groups.…”
Section: Biochemical Indicatorssupporting
confidence: 87%
“…At the same time, there was no difference between GSH-Px levels in the high salinity group S3 and the GSH-Px levels of the freshwater group. These results are similar to those of studies on turbot (Scophthalmus maximus) [22], where CAT and GSH-Px work together to degrade hydrogen peroxide in high-salinity environments. In low-salinity environments where fish do not experience significant oxidative stress, GSH-PX does not rise to the same level as in freshwater groups.…”
Section: Biochemical Indicatorssupporting
confidence: 87%
“…However, the excessive accumulation of ROS occurs when ROS production exceeds the capacity of the antioxidant system or when the ROS detoxifying system is compromised, which causes severe damage to the structure and function of the cell membrane leading eventually to cell death [ 21 , 29 ]. Numerous previous studies have demonstrated that saline-alkaline exposure leads to the excessive accumulation of ROS and causes oxidative stress in aquatic animals [ 30 ]. Antioxidant enzymes are important components of the fish’s antioxidant system, and the SOD–CAT–GSH-Px cascade serves as the first line of defense against ROS [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ikan air tawar yang dipindahkan ke dalam media bersalinitas tinggi akan cenderung memasukkan garam-garam ke dalam tubuhnya. Ikan air tawar yang diadaptasikan ke media air bersalinitas lebih tinggi dari tubuhnya memperlihatkan perubahan konsentrasi garam tubuh secara berangsur-angsur akibat kontrol permeabilitas oleh hormon dan sistem saraf otomatis terhadap lingkungan baru dan pengaruh langsung sel-sel tubuhnya (Hayuningtyas et al, 2016;Jiang et al, 2022;dan Sitio et al, 2017). Kondisi salinitas awal yang tinggi dengan peningkatannya yang tinggi pula mengakibatkan benih ikan nila salin tidak mengalami pertumbuhan, bahkan cenderung mengalami penurunan laju pertumbuhan harian.…”
Section: Hasil Dan Pembahasanunclassified